Professional burnout and job performance in collaborators of microfinance entities in the Junín region - Aguilar-Tinoco, Jhordana A. (2023)
As a result of the COVID-19 pandemic, high levels of professional burnout were generated associated with low levels of performance and, therefore, productivity in various business sectors. The objective of the study was to measure the relationship between professional burnout and job performance in employees of microfinance entities in the Junin region. The research was framed within the guidelines of the quantitative paradigm and the criteria of a non-experimental-cross-sectional design and was also of a basic observational type and correlational level. The sample was made up of 190 collaborators from different microfinance entities in the Junin region. The technique used was the survey, to measure professional burnout the Maslach exhaustion inventory was used and to measure job performance the job performance scale was used. The data were analyzed with SPSS version 25 for Windows. The results showed the existence of a negative correlation of -0.224 between professional burnout and job performance with a p-value of 0.027. Therefore, it is concluded that there is a significant negative relationship between professional burnout and job performance in employees of microfinance entities in the Junin region.